Selenite Reduction by Proteus sp. YS02: New Insights Revealed by Comparative Transcriptomics and Antibacterial Effectiveness of the Biogenic Se0 Nanoparticles - Wang, Yuting; Ye, Qing; Sun, Yujun; Jiang, Yulu; Meng, Bo; Du, Jun; Chen, Jingjing; Tugarova, Anna V.; Kamnev, Alexander A.; Huang, Shengwei (Frontiers in Microbiology, 2022)
Biotransformation of selenite by microorganisms is an effective detoxification (in cases of dissimilatory reduction, e.g., to Se0) and assimilation process (when Se is assimilated by cells). However, the current knowledge of the molecular mechanism of selenite reduction remains limited. In this study, a selenite-resistant bacterium was isolated and identified as Proteus sp. YS02. Strain YS02 reduced 93.2% of 5.0 mM selenite to selenium nanoparticles (SeNPs) within 24 h, and the produced SeNPs were spherical and localized intracellularly or extracellularly, with an average dimension of 140 ± 43 nm. The morphology and composition of the isolated and purified SeNPs were characterized using dynamic light scattering (DLS), scanning electron microscopy (SEM) with energy-dispersive X-ray (EDX) spectrometry, and Fourier transform infrared (FTIR) spectroscopy. FTIR spectroscopy indicated the presence of proteins, polysaccharides, and lipids on the surface of the isolated SeNPs. Furthermore, the SeNPs showed excellent antimicrobial activity against several Gram-positive and Gram-negative pathogenic bacteria. Comparative transcriptome analysis was performed to elucidate the selenite reduction mechanism and biosynthesis of SeNPs. It is revealed that 197 genes were significantly upregulated, and 276 genes were significantly downregulated under selenite treatment. Gene ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed that genes associated with ABC transporters, sulfur metabolism, pentose phosphate pathway (PPP), and pyruvate dehydrogenase were significantly enhanced, indicating selenite is reduced by sulfite reductase with PPP and pyruvate dehydrogenase supplying reducing equivalents and energy. This work suggests numerous genes are involved in the response to selenite stress, providing new insights into the molecular mechanisms of selenite bioreduction with the formation of SeNPs.